Burden of obesity in the Eastern Mediterranean Region: findings from the Global Burden of Disease 2015 study - El Bcheraoui, Charbel; Jonas, Jost B.; Mokdad, Ali (International journal of public health, 2018)
OBJECTIVES: We used the Global Burden of Disease (GBD) 2015 study results to explore the burden of high body mass index (BMI) in the Eastern Mediterranean Region (EMR). - METHODS: We estimated the prevalence of overweight and obesity among children (2-19 years) and adults (≥20 years) in 1980 and 2015. The burden of disease related to high BMI was calculated using the GBD comparative risk assessment approach. - RESULTS: The prevalence of obesity increased for adults from 15.1% (95% UI 13.4-16.9) in 1980 to 20.7% (95% UI 18.8-22.8) in 2015. It increased from 4.1% (95% UI 2.9-5.5) to 4.9% (95% UI 3.6-6.4) for the same period among children. In 2015, there were 417,115 deaths and 14,448,548 disability-adjusted life years (DALYs) attributable to high BMI in EMR, which constitute about 10 and 6.3% of total deaths and DALYs, respectively, for all ages. - CONCLUSIONS: This is the first study to estimate trends in obesity burden for the EMR from 1980 to 2015. We call for EMR countries to invest more resources in prevention and health promotion efforts to reduce this burden.
Published online: 3 August 2017
Gesehen am 14.05.2020
GBD 2015 Eastern Mediterranean Region Adolescent Health Collaborators: C. El Bcheraoui, J.B. Jonas, A.H. Mokdad [und 100 weitere]